In vitro growth pattern of rumen microbes on cellulosic feeds using buffalo and cattle rumen liquor - SANGWAN, D C; KUMAR, SHIV; SINGH, SADHANA; BHATIA, S K; DULAR, R K (The Indian Journal of Animal Sciences, 2014)
The growth pattern of anaerobes was studied by using rumen mixed culture from cattle and buffalo under in vitro rumen fermentation up to 431 hr of 9 cellulosic feeds (CP 2.1 to 20.3%, NDF 50.3 to 77.7%, ADF 38.9 to 52.3%, cellulose 26.5 to 39.7%). The competitive seprobic ability (CSA) of rumen microbes on such feed revealed relatively higher (P<0.05) cellular growth, in descending order, on sorghum stover, oat hay, wheat straw and berseem hay than that on paddy straw, chickpea straw, lucerne hay and pearlmillet stover in buffalo and cattle. Sorghum stover, wheat straw, sugarcane bagasse and hays (oat, lucerne, berseem) proliferated more (P<0.05) microbial growth in buffalo than cattle. The growth of microbes in cattle surpassed than that in buffalo due to paddy straw and pearlmillet stover. A contimlous lag phase of cellularÂ multiplication between 27 hr (wheat straw, paddy straw, sorghum stover) to 91 hr (berseem hay) was followed by stationary and decline in microbial growth. The rumen gas pool size which did not differ between ruminant species was least due to the fermentation of chickpea straw (8.6,9.5 ml/0.5g) and was recorded to be highest (16.2, 16.5 ml/0.5g for buffalo and cattle respectively) on oat hay. Significant correlations between rumen microbial growth and gas pool size were established.